2016
DOI: 10.3906/biy-1501-52
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic activity of sanguinarine in C32 human amelanotic melanoma cells

Abstract: Sanguinarine, an alkaloid present in various medicinal plants, has been associated with detrimental effects on different types of cancer cells. The aim of our study was to analyze the cytotoxic effects of sanguinarine on C32 human amelanotic melanoma cells. The cells were exposed to various concentrations of sanguinarine (0.5, 1, and 2 µM) for 24 h and displayed a dose-dependent decrease in cell viability; the sanguinarine-induced oxidative stress in C32 cells affected the activity of antioxidant enzymes and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…Kemeny-Beke et al (2006), using human primary cells of the OCM-1 line, reported that the concentration of 8 μg/ml of sanguinarine induces the formation of swollen and enlarged cells, as well as shrunken cells with apoptotic morphology [16]. Similar results were obtained by Cojocaru et al (2016) on C32 amelanotic melanoma cell line [14]. In turn, Serafim et al (2008) showed that 8 μM initiates rounding of K1735-M2 mouse melanoma cells and changes in the cell nucleus with clearly noticeable chromatin condensation [17].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Kemeny-Beke et al (2006), using human primary cells of the OCM-1 line, reported that the concentration of 8 μg/ml of sanguinarine induces the formation of swollen and enlarged cells, as well as shrunken cells with apoptotic morphology [16]. Similar results were obtained by Cojocaru et al (2016) on C32 amelanotic melanoma cell line [14]. In turn, Serafim et al (2008) showed that 8 μM initiates rounding of K1735-M2 mouse melanoma cells and changes in the cell nucleus with clearly noticeable chromatin condensation [17].…”
Section: Discussionsupporting
confidence: 53%
“…Similar results were obtained by Cojocaru et al ( 2006), who assessed the cytotoxic effect of SAN on cells of the C32 amelanotic melanoma cell line. The doses of alkaloid used were 0.5, 1, and 2 μM and generated a dose-dependent decrease in cell survival [14]. In turn, Tuzimski et al (2021) tested SAN on three types of melanoma cells -A375, G361, and SKMEL3.…”
Section: Discussionmentioning
confidence: 99%